Implementación de un sistema de control de inventarios físicos en la empresa Ecuafar distribuidora farmacéutica - Romero Albuja, Mayra Cristina (2012)
We performed the implementation of a control system and physical inventory management for Pharmaceutical Distributor Ecuafar, with the main objective to minimize the losses that occur due to differences in inventory, after analyzing various methods of inventory control and management concluded Control the ABC method is the method that best suits the structure of reality and Pharmaceutical Distributor Ecuafar. By implementing this method in a high percentage reduced losses, obtaining better control and physical inventory management which creates efficiency and effectiveness not only in this area, the results obtained here further reflected in the financial area of the Distributor.